Shadowcasting tourism knowledge through media: Self-driving sex cars?. (November 2020) - Cohen, Scott; Stienmetz, Jason; Hanna, Paul; Humbracht, Michael; Hopkins, Debbie
Abstract: Tourism is central to late-modern life, and tourism research that threatens this centrality is prone to media attention. Framed by sociotechnical transitions theory, we introduce the concept of 'shadowcasting' to show how tourism knowledge disseminated through the media, combined with public comments on its reporting, cast shadows that co-constitute imagined futures. We illustrate shadowcasting through a mixed method approach that demonstrates how media reporting and public comments on a recent paper on autonomous vehicles in tourism emerged and diverged from the original paper. Our findings reveal that issues around sex and terrorism were sensationalised, generating diverse public discourses that challenge linear visions of future transport efficiency. Our concluding discussion indicates other tourism research contexts that are most inclined to shadowcasting. Highlights: Reveals how tourism research is bound up in future-making through media reporting. Introduces and develops the concept of 'shadowcasting'. Shows this process through a recent paper on autonomous vehicles in tourism. Finds that issues around sex and terrorism were sensationalised. Indicates other tourism research contexts inclined to shadowcasting.